2019
DOI: 10.1093/infdis/jiz390
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Respiratory Syncytial Virus Fusion (F) Protein Nanoparticle Vaccine in Healthy Third-Trimester Pregnant Women and Their Infants

Abstract: Background Respiratory syncytial virus (RSV) is the leading cause of infant lower respiratory tract disease and hospitalization worldwide. Methods Safety and immunogenicity of RSV fusion (F) protein nanoparticle vaccine or placebo were evaluated in 50 healthy third-trimester pregnant women. Assessments included vaccine tolerability and safety in women and infants, and RSV-specific antibody measures in women before and after v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…Lastly, an aluminum-adjuvanted RSV F-protein nanoparticle vaccine (Novavax, Inc., Gaithersburg, Maryland, US) was evaluated in women of childbearing age [59] and in a phase II study in pregnant women prior to being the first vaccine evaluated in a phase III clinical trial, seeking an indication for administration in pregnancy. The phase II study demonstrated that the vaccine was safe and well tolerated, and induced significantly higher concentrations of both anti F-IgG, but also neutralizing antibodies and Palivizumab competing antibodies [60]. This study also found that maternal antibody responses peaked at 14 days after vaccination, and that an interval of ≥30 days from maternal vaccination to delivery maximized transplacental antibody transfer for all measured antibodies [60].…”
Section: Maternal Immunization For the Prevention Of Rsv In Infantssupporting
confidence: 51%
See 1 more Smart Citation
“…Lastly, an aluminum-adjuvanted RSV F-protein nanoparticle vaccine (Novavax, Inc., Gaithersburg, Maryland, US) was evaluated in women of childbearing age [59] and in a phase II study in pregnant women prior to being the first vaccine evaluated in a phase III clinical trial, seeking an indication for administration in pregnancy. The phase II study demonstrated that the vaccine was safe and well tolerated, and induced significantly higher concentrations of both anti F-IgG, but also neutralizing antibodies and Palivizumab competing antibodies [60]. This study also found that maternal antibody responses peaked at 14 days after vaccination, and that an interval of ≥30 days from maternal vaccination to delivery maximized transplacental antibody transfer for all measured antibodies [60].…”
Section: Maternal Immunization For the Prevention Of Rsv In Infantssupporting
confidence: 51%
“…The phase II study demonstrated that the vaccine was safe and well tolerated, and induced significantly higher concentrations of both anti F-IgG, but also neutralizing antibodies and Palivizumab competing antibodies [60]. This study also found that maternal antibody responses peaked at 14 days after vaccination, and that an interval of ≥30 days from maternal vaccination to delivery maximized transplacental antibody transfer for all measured antibodies [60]. This study allowed the progression to a global phase III efficacy clinical trial to evaluate this maternal vaccine for the protection of RSV in infants.…”
Section: Maternal Immunization For the Prevention Of Rsv In Infantsmentioning
confidence: 99%
“…Studies on RSV-F protein in pregnant women have shown that these vaccines are safe and immunogenic in pregnant women (219,220). The use of these RSV vaccines in healthy pregnant women is further supported by evidence that maternal RSV neutralizing antibodies are efficiently transferred from the mother to the newborn, with levels at delivery that are similar or higher in the cord blood compared with the maternal blood at delivery (219,220).…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
“…The Global Alignment of Immunization Safety Assessment in Pregnancy (GAIA) project was established, and since 2014, GAIA [3], utilizing Brighton Collaboration methodology, has developed and published case definitions and guidelines for data collection, analysis, and presentation of maternal immunization safety data in trials involving pregnant women for twenty-one obstetric and neonatal terms [4]. These case definitions and tools have been adopted in recent maternal immunization studies to evaluate maternal and neonatal outcomes, including use in a recent Phase III maternal immunization trial [5,6].…”
Section: Introductionmentioning
confidence: 99%